2021
DOI: 10.33206/mjss.865460
|View full text |Cite
|
Sign up to set email alerts
|

Uluslararası Göçün İşsizlik Üzerindeki Etkisi: Avrupa Ülkelerine Yönelik Ampirik Bir Analiz

Abstract: Europe attracts attention in terms of geography where immigrant movements are intense. The region received international migrant heavily because of World War II, the fall of the Berlin Wall, and its connections with Africa and Latin America. After the 2000s, the war, civil conflict and political instability in especially Afghanistan, the Middle East and Africa increased the migration movements. Migration movements have important social and political consequences as well as economic consequences. The most essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In addition, migration is a temporary or permanent action depending on different times and places (Türkyılmaz et al, 1998: 25). While some relocate in search of food, water, or security, others may do so in search of better health, education, or social standing (Gündoğmuş andBayır, 2021: 2205). Labor migration, on the other hand, generally occurs as the use of unskilled labor in developing or underdeveloped countries in the labor force in developed countries for higher wages (Sugözü and Yaşar, 2021: 349).…”
Section: A Definition and Causes Of International Migrationmentioning
confidence: 99%
“…In addition, migration is a temporary or permanent action depending on different times and places (Türkyılmaz et al, 1998: 25). While some relocate in search of food, water, or security, others may do so in search of better health, education, or social standing (Gündoğmuş andBayır, 2021: 2205). Labor migration, on the other hand, generally occurs as the use of unskilled labor in developing or underdeveloped countries in the labor force in developed countries for higher wages (Sugözü and Yaşar, 2021: 349).…”
Section: A Definition and Causes Of International Migrationmentioning
confidence: 99%
“…Using panel regression analysis, Gündoğmuş and Bayır (2021) looked at the impact of international immigration on unemployment in 27 European nations between 2000 and 2017, and they found no statistically significant relationship between the variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the problem is not so simple, as there are also studies that show an entirely different picture. For example, from their analysis of data from 27 EU countries in 2000-2017 Gündoğmuş and Bayir (2021) concluded that international migration does not have a statistically significant effect on unemployment.…”
Section: Unemployment and Its Determinants In Theoretical Contextmentioning
confidence: 99%